2019
DOI: 10.5897/ajest2019.2757
|View full text |Cite
|
Sign up to set email alerts
|

Future evolution of surface temperature extremes and the potential impacts on the human health in Senegal

Abstract: Climate change impacts negatively vulnerable regions such as West African countries like Senegal, through an increase of climate extremes. The objectives of this study is to analyze the future evolution of the extreme temperature events and their impacts on human health in Senegal during the cold (DJF), hot (MAM) and wet seasons (JAS) under the greenhouse gas scenarios RCP4.5 and RCP8.5 using Climate projections of five (5) regional climate models (RCMs) of the Coordinated Regional Climate Downscaling Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…The HI values obtained during the DJF period correspond to the symptom band I and that of the MAM, JJA, and SON seasons to the symptom band II ( Table 2). These results are in agreement with the findings of Meehl and Tebaldi (2004) and Sarr et al (2019). The difference between the two versions of the model shows that the accumulation of mineral dust in the atmosphere results in a decrease of the heat index especially in the northern Sahel during the MAM period, over the western Sahel during JJA, and over the central, the southern, and the northeastern parts of the Sahel during the SON period traducing a decrease of health risks.…”
Section: Effects Of Dust Emissions On Temperature Extremes Over the Ssupporting
confidence: 90%
See 3 more Smart Citations
“…The HI values obtained during the DJF period correspond to the symptom band I and that of the MAM, JJA, and SON seasons to the symptom band II ( Table 2). These results are in agreement with the findings of Meehl and Tebaldi (2004) and Sarr et al (2019). The difference between the two versions of the model shows that the accumulation of mineral dust in the atmosphere results in a decrease of the heat index especially in the northern Sahel during the MAM period, over the western Sahel during JJA, and over the central, the southern, and the northeastern parts of the Sahel during the SON period traducing a decrease of health risks.…”
Section: Effects Of Dust Emissions On Temperature Extremes Over the Ssupporting
confidence: 90%
“…During the wet season (JJA) and the SON period, the model simulates a north-south gradient with the lowest humidex located over the southern Sahel ( Figures 11C,D). The strongest values (>32°C) of this indice are recorded over the southern Sahel during the MAM period ( Figure 11B) and over the northern Sahel during the JJA and SON periods ( Figures 11C,D) in agreement with Sarr et al (2019) traducing evident discomfort (Category B and C in Table 3). The difference between both versions of the model shows that the dust impact is to decrease the humidex especially in the northwestern part of the Sahel during the DJF and MAM periods and over the central and the northeastern parts of the Sahel during the JJA and SON periods.…”
Section: Effects Of Dust Emissions On Temperature Extremes Over the Ssupporting
confidence: 61%
See 2 more Smart Citations
“…For example, in reviews of case studies, by Campbell et al (2018) and Mora et al (2017), four studies were found for Africa and seven for South America. More recent works include studies for South Africa (Wright et al 2019) Senegal (Sarr et al 2019), and Brazil (Zhao et al 2018). The dataset developed by Guo et al (2018) included no data for Africa and limited data for Brazil, Chile, and Columbia.…”
Section: Health Impacts Of Heatwavesmentioning
confidence: 99%